Comparison of Esophageal Function Tests in Chinese Patients with Functional Heartburn and Reflux Hypersensitivity - Feng Gao; Yan Gao; Xue Chen; Jie Qian; Jie Zhang (Gastroenterology Research and Practice)
Objective. To investigate the differences in the results of esophageal function tests for functional heartburn (FH) and reflux hypersensitivity (RH). Methods. Patients with FH and RH and healthy volunteers (HVs) from the Department of Gastroenterology, Beijing Anzhen Hospital and Beijing Chao-Yang hospital, who underwent high-resolution manometry and impedance (HRIM), and 24-hour multichannel intraluminal impedance and pH recording (MII/pH) between 2014 and 2016, were enrolled in this study. Results. 36 HV, 147 FH patients, and 91 RH patients were enrolled. The postreflux swallow-induced peristaltic wave index (PSPW index) and mean nocturnal baseline impedance (MNBI) values were significantly lower in RH than in FH and HV. The ineffective esophageal motility (IEM), fragmented peristalsis rates, total bolus exposure, proximal total reflux events, and distal total reflux events were significantly greater in RH than in FH and HV. Conclusions. Compared to HV and FH patients, RH patients exhibited greater IEM and fragmented peristalsis rates, a greater total bolus exposure, more proximal total and distal total reflux events, and reduced chemical clearance and mucosal integrity. By using the above described parameters, HRIM and MII/pH assays could be used to correctly classify RH and FH and hence allow physicians to provide adequate relief from associated symptoms.